Analysis of the Land Dispute Between the Residents of Banjar Sari Village and Pt Bumi Gema Gempita in East Merapi District, Lahat Regency - Nadia Utami; Norma Juainah; Erik Darmawan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research is motivated by the land dispute between the people of Banjar Sari Village and PT Bumi Gema Gempita which has been going on since 2006 and until now has not been resolved fairly. This conflict is rooted in the difference in claims between the community that controls the land for generations and the company which bases its activities on the formal legality of the 2010 Mining Business Permit (IUP). This study aims to analyze the causes and dynamics of land disputes using an environmental political perspective. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study show that land disputes are influenced by three main factors, namely inconsistencies between AMDAL data and the determination of IUP (science factors), the dominance of the company's economic interests in land that has mining value (economic factors), and the weak application of the principles of justice, transparency, and social responsibility (value and ethical factors). In addition, this conflict also has significant social impacts on society, such as the emergence of a sense of injustice, a decrease in the level of trust in the government and the legal system, and the disruption of social relations in the community. Thus, it can be concluded that this land dispute reflects the inequality of power relations in the management of agrarian resources, so that its resolution is not enough only through a formal legal approach, but also requires an approach that considers social justice and recognition of the rights of local communities.